2010
DOI: 10.1128/jb.01082-09
|View full text |Cite
|
Sign up to set email alerts
|

fpr , a Deficient Xer Recombination Site from a Salmonella Plasmid, Fails To Confer Stability by Dimer Resolution: Comparative Studies with the pJHCMW1 mwr Site

Abstract: Salmonella plasmid pFPTB1 includes a Tn3-like transposon and a Xer recombination site, fpr, which mediates site-specific recombination at efficiencies lower than those required for stabilizing a plasmid by dimer resolution. Mutagenesis and comparative studies with mwr, a site closely related to fpr, indicate that there is an interdependence of the sequences in the XerC binding region and the central region in Xer site-specific recombination sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Figure 3C shows that the level of resolution of dimers containing pbr1 or pbr2 is considerably lower than those of the controls containing cer or mwr. We have shown before that levels of resolution as low as that one exhibited by mwr-harboring dimers in cells grown in L broth containing 0.5% NaCl are not enough to confer stability by multimer resolution (34,35). As shown in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Figure 3C shows that the level of resolution of dimers containing pbr1 or pbr2 is considerably lower than those of the controls containing cer or mwr. We have shown before that levels of resolution as low as that one exhibited by mwr-harboring dimers in cells grown in L broth containing 0.5% NaCl are not enough to confer stability by multimer resolution (34,35). As shown in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…These sites have been detected so far only on two natural plasmids, pJHCMW1 (22) and pFPTB1 (29), in a Salmonella enterica serovar Typhimurium isolate and in a K. pneumoniae isolate, respectively (22,29), each carrying a transposon inserted about 20 bp downstream of Xer. It has been postulated that multimer resolution of these plasmids is provided by the transposon resolvase besides the Xer system, suggesting that they form a group of plasmids whose stability is significantly enhanced by transposon acquisition (28). pKBuS13 is, to our knowledge, the third natural plasmid belonging to this group.…”
Section: Resultsmentioning
confidence: 99%
“…pKBuS13 is, to our knowledge, the third natural plasmid belonging to this group. However, its Xer recombination system is probably ineffective because the fpr site is the less efficient among those detected in the core region (28), and, most importantly, its accessory region is broken by Tn4401b insertion. Xer system inactivity is supported by two observations: (i) under nonselective conditions, both K. pneumoniae KBu-1 and E. coli JM101 lost pKBuS13 at approximately the same rate of pUC19, which lacks an Xer recombination site and is randomly partitioned during cell division (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3) (78). It is of interest that numerous Xer site-specific recombination sites with identical deficiency in the ARG box have been detected and in some cases experiments demonstrated that they mediate dimer resolution at low efficiency (81). This fact, taken together with other findings like the presence of Xer site-specific recombination sites flanking blaOXA genes in Acinetobacter plasmids (90, 93-96) or the presence of different DNA fragments flanked by a Xer recombination site and an oriT in otherwise identical plasmids (54, 88) leads to the idea that not all Xer recombination sites stabilize plasmids by multimer resolution but may play other, or additional, roles related to plasmid evolution.…”
Section: Small Plasmidsmentioning
confidence: 99%